Steady state-VEP based BCI for control gripping of a Robotic hand - Al-maqtari, M.T.; Taha, Z.; Moghavvemi, M. (2009)
Brain Computer Interface (BCI) is system that established a direct connection between the human brain and computer thus providing an additional communication channel. Nowadays, they are used in a broad filed of application. In the current application, a SSVEP is used to control a robotic hand through a BCI system. This paper present the preliminary results from two subjects which indicate the characteristics of SSVEP harmonics amplitude differ from one subject to another.